ANALISIS POLA IKAT PADA TARI JEPIN TALI BUI DI DESA KARIMUNTING KABUPATEN BENGKAYANG - Midya Yulika; Ismunandar Ismunandar; Winda Istiandini (Universitas Tanjungpura, 2019)
AbstractThe problems of this research were ‘how was the relationship of dance movement in the process of binding pattern and the meaning of how to knit binding pattern in Jepin Tali Bui dance in Karimunting and the meaning contained in the presentationvillage of Sungai Raya Kepulauan District of Bengkayangand the implementation of learning art Subject.The method used in this research was descriptive method in form of qualitative design. The approach of this research was ethnocoreology which was a multidisciplinary science that was used more than one discipline.The data used in this research were the results of observation, interviews, and documantationsThe analysis of the of how to knit binding pattern and the meaning contained in the presentationmeaning of binding pattern of Jepin Tali Bui dance based on the interviews of the interviwees and documenting it.The meaning of binding pattern based on the story in Jepin Tali Bui dance relates to human life, namely the life of honesty, mutual respect, no envy, and envy towards human beings. Based on the interview with Mrs. Suraddmi, she said that the meaning of the direction of the binding pattern from top to down there was no special meaning, however it had a a narrative value that the soldier tied from top to down so that the soldier hard to escape and rebel. The results of this research were expected to be implementation of learning art Subject in form of lesson plans in the teaching learning process of art and cultre subject to the seventh grade of Junior High School.Keywords: Binding Pattern, Bengkayang, Jepin Tali Bui Dance